Bystander Effect Induced by UVC Radiation in Chinese hamster V79 cells. (5th March 2014) - Wu, Shengwen; Jin, Cuihong; Lu, Xiaobo; Yang, Jinghua; Liu, Qiufang; Qi, Ming; Lu, Shuai; Zhang, Lifeng; Cai, Yuan
Abstract In past decades, researches on radiation‐induced bystander effect mainly focused on ionizing radiation such as α‐particle, β‐particle, X‐ray and γ‐ray. But few researches have been conducted on the ability of ultraviolet (UV) radiation‐induced bystander effect, and knowledge of UVC‐induced bystander effect is far limited. Here, we adopted medium transfer experiment to detect whether UVC could cause bystander effect in Chinese hamster V79 cells. We determined the cell viability, apoptosis rate, chromosome aberration and ultrastructure changes, respectively. Our results showed that: (1) the viability of UVC‐irradiated V79 cells declined significantly with the dosage of UVC; (2) similar to the irradiated cells, the main death type of bystander cells cultured in irradiation conditioned medium (ICMs) was also apoptosis; (3) soluble factors secreted by UVC‐irradiated cells could induce bystander effect in V79 cells; (4) cells treated with 4 h ICM collected from 90 mJ cm−2 UVC‐irradiated cells displayed the strongest response. Our data revealed that UVC could cause bystander effect through the medium soluble factors excreted from irradiated cells and this bystander effect was a novel quantitative and kinetic response. These findings might provide a foundation to further explore the exact soluble bystander factors and detailed mechanism underlying UVC‐induced bystander effect.